Pengaruh Model PBL terhadap Hasil Belajar Kognitif Biologi Siswa - Khacera Juliyanti; Nopriyeni Nopriyeni (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model on the Biological Cognitive Learning Outcomes of students at SMA Negeri 2 Rejang Lebong. This type of research is a quasi-experimental research (quasi experimental research) with a Randomized Control-Group Pretest-Posttest design. Technique of sample used is a random sampling technique. The data collection techniques in this study consisted of tests in the form of pretest and posttest. The results of this study indicate that there is an effect of the Problem Based Learning (PBL) learning model on the cognitive biology learning outcomes of class XI students at SMAN 02 Rejang Lebong, namely the significance level obtained using SPSS 21 which shows the t-test <0.05, which is 0.000. Based on the results, it can be concluded that the Problem Based Learning (PBL) learning model affects the cognitive biology learning outcomes of class XI students at SMAN 02 Rejang Lebong. Keywords: Cognitive Learning Outcomes, Problem Based Learning (PBL)